Introducing a new cadre into Uganda’s health care system: Lessons learnt from the implementation process - Amandu, Gerald M.; Uys, Leana R.; Mwizerwa, Joseph; Erejo, Alex; Cheruto, Irene A.; Chota, Margaret (Procedia-Social and Behavioral Sciences, 2013)
Uganda introduced Registered Comprehensive Nursing (RCN) and Enrolled Comprehensive Nursing (ECN) training programs in 1994 and 2003 respectively, to create certificate and diploma level cadre of nurses with competencies in general nursing, midwifery, public health, psychiatry, paediatrics and management. This paper is based on an evaluation study undertaken to assess how the programs were implemented including stakeholders’ perceptions about the graduates. Despite being relevant, the implementation process of both programs failed to meet acceptable standards. We conclude that introducing a new cadre of nurses without proper preparation hinders realization of their full potential including their contribution to the healthcare system.